Західноукраїнська інтелігенція у таборах СССР, 1930-ті рр.: людські біографії у контексті “перековки” - Рубльов, О. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2004)
Using the little known archival documents including the one of the former special service of the USSR and Soviet Ukraine, the author depicted the camp period in the biographies of Western Ukrainian intelligentsia convicted by faked cases, such as “Ukrainian national center”, “Ukrainian war organization”, “Polish war organization” and others.